Demonstrasi Pengolahan Abon Ikan Lele Sebagai Ide Wirausaha di Kelurahan Ulak Karang Utara - Rizka Ramadibta; Lya Heldya Maryssa Manulang; Takkas Abelio Napitupulu; Ninuk Purnaningsih (Jurnal Pusat Inovasi Masyarakat (PIM), 2021)
Catfish is a fish that is widely consumed by Indonesian people. However, some people are still reluctant to consume them. One of them is because it smells fishy. The creativity of food producers to cover this deficiency is needed in this fish processing method. One of the catfish processing that can be done is shredded catfish. Shredded catfish is one of the processed fishery products made from fish meat, or fish processed with seasonings. Shredded catfish is processed by boiling, frying, pressing or separating the oil. The resulting product has a good taste and relatively long durability. Processing catfish into shredded catfish will increase the quality value of the food product. Shredded catfish can be an alternative food product for people who want to consume catfish without fishy smell with an attractive appearance. In addition, shredded catfish can also be a profitable entrepreneurial field for the community. Keywords: Catfish, creativity, demonstration, entrepreneur, shredded